'How Silver-Sweet Sound Lovers' Tongues': The music of love and death in Franco Zeffirelli's Romeo and Juliet. Issue 1 (1st April 2014) - Lin, Samantha
This article examines the ways in which the musical 'love theme' in Franco Zeffirelli's Romeo and Juliet (1968) plays a crucial role in the careful negotiation of additions and subtractions in terms of content, visuals, and audio alike—negotiations made necessary by the shift of medium from drama to film. Introduced as a song entitled 'What Is a Youth?' in the film's diegesis, the 'love theme' is a popular tune that has since been covered extensively in various versions and arrangements. However, despite the name attributed to the cue, the 'love theme' does not only represent the titular characters' passion, but also the result of such love: their deaths. By considering the function of the 'love theme' in relation to both notions of love and death, this article argues that the soundtrack is crucial in supporting Zeffirelli's interpretation, not only in terms of creating an emotional landscape for the film, but also on a wider level in consolidating and translating the ideas of Shakespearean tragedy.